Systematic characterization of extracellular vesicles from potato (Solanum tuberosum cv. Laura) roots and peels: biophysical properties and proteomic profiling - Ekanayake, Gayandi; Piibor, Johanna; Midekessa, Getnet; Godakumara, Kasun; Dissanayake, Keerthie; Andronowska, Aneta; Bhat, Rajeev; Fazeli, Alireza (Frontiers in Plant Science, 2024)
Introduction Extracellular vesicles (EVs) facilitate inter and intra-species/kingdom communication through biomolecule transfer, including proteins and small RNAs. Plant-derived EVs, a hot topic in the field, hold immense capability both as a potential biomarker to study plant physiology and as a biomaterial that can be mass-produced to be used in various industries ranging from cosmetics and food additives to biological pesticides. However, a systematic characterization of plant EVs is required to establish a foundation for further applications and studies. Methods In this study, EVs were enriched from hydroponically cultivated potato plants (Solanum tuberosum, cv. Laura). We isolated EVs from root exudates and the apoplastic wash of potato peels using vacuum infiltration. These EVs were then systematically characterized for their biophysical and chemical properties to compare with standard EV characteristics and to explore their roles in plant physiology. Results Biophysical and chemical analyses revealed morphological similarities between potato root and peel-derived EVs. The average diameter of root-derived EVs (164.6 ± 7.3 nm) was significantly larger than that of peel-derived EVs (132.2 ± 2.0 nm, p < 0.004). Liquid chromatography–mass spectrometry (LC-MS) demonstrated substantial protein enrichment in purified EVs compared to crude samples, with a 42% enrichment for root EVs and 25% for peel EVs. Only 11.8% of the identified proteins were common between root and peel EVs, with just 2% of significantly enriched proteins shared. Enriched pathways in both EV proteomes were associated with responses to biotic and abiotic stress, suggesting a defensive role of EVs in plants. Discussion With further experimentation to elucidate the specific methods of communication, these findings increase the details known about plant EVs in terms of their physical and chemical characteristics and their potential functions, aiding in sustainable agricultural waste utilization for large-scale EV production, aligning with the concept of “valorization”.